Prevalence and Risk Factors of Human Papillomavirus Infection in Asymptomatic Women in a Venezuelan Urban Area - Núñez-Troconis, José; Delgado, Mariela; González, Julia; Mindiola, Raimy; Velásquez, Jesvy; Conde, Betty; Whitby, Denise; Munroe, David J (Investigación Clínica, 2009)
The purpose of this study was to investigate the prevalence and risk factors of genital human papillomavirus (HPV) infection in asymptomatic women, using the HPV DNA Hybrid Capture 2 (HC2) test. Three hundred and two women who attended the Out-Patient Gynecological Clinic of a tertiary level hospital, in a Venezuelan urban area, were selected for the study. A pap smear, a cervical swab for HC2 and gynecological exam were performed to each patient. The HC2 testing showed that 47 samples (15.6%) were positive to HPV. Forty patients (13.2%) were positive to high risk-HPV (HR-HPV) and 11 (3.6%) were positive to low-risk-HPV (LR-HPV). The prevalence of HPV infections was higher for women under 35 years (51.1%; p < 0.02), and decreased to 6.4% for women Â³ 65 years old. Women who had not finished high school had a higher prevalence of HPV infection (p < 0.035). Twenty six (42.6%) of 61 pathological Pap smears were positives to HPV infection. A statistically significant difference was found when HPV infection was compared in normal and abnormal Pap smear (HSIL+LSIL; p